Penyuluhan Jual Beli Kredit Secara Syariah Pada Pelaku UMKM Di Desa Pematang Serai Langkat - Heriyati Chrisna Chrisna; Hernawaty Hernawaty; Noviani Noviani (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
In the Qur'an, Allah has affirmed that man spends his wealth in the right way according to sharia, as contained in Surah Al-Baqarah verses 195, 212 and 275 and Surah An-Nisa verse 29 which can be used as a proposition about the halal buying and selling of credit although not specifically because indeed in the Qur'an there is not a single verse that specifically explains the law of this transaction,  But this proposition can at least make Muslims calmer because of the general and universal meaning. The devotion program in the form of counseling runs smoothly and is followed enthusiastically by MSME actors Pucuk Serai. The program that is run has been able to motivate MSME actors Pucuk serai Pematang Serai village to understand sharia law from credit buying and selling transactions. In the future it is recommended that re-counseling with other materials, especially muamalah.